Measurements and Analytical Computer-Based Study of CMOS Inverters and Schmitt Triggers - Umesh Kumar (Active and Passive Electronic Components)
Modified CMOS inverters with three and four transistors have been made. Two varieties of CMOS Schmitt Triggers have been considered. CMOS Schmitt Trigger with wide hysteresis has been obtained. Complete detailed theoretical, experimental and computer based results are derived and exhibited.